2017
DOI: 10.2169/internalmedicine.56.6910
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Bone Mineral Density in Men with Chronic Obstructive Pulmonary Disease Classified According to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) Combined Chronic Obstructive Pulmonary Disease (COPD) Assessment System

Abstract: Objective Osteoporosis, which is now recognized as a major comorbidity of chronic obstructive pulmonary disease (COPD), must be diagnosed by appropriate methods. The aims of this study were to clarify the relationships between bone mineral density (BMD) and COPD-related clinical variables and to explore the association of BMD with the updated Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification in men. Methods We enrolled 50 Japanese men with clinically stable COPD who underwent dual-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The logistic regression analyses confirmed that airway obstruction categories were associated with osteopenia/OP, even after adjustment for potential confounding factors, showing that postmenopausal women with COPD may have a higher risk of osteopenia/OP. Our finding may be supported by observations by Sakurai et al 8 , who found that the prevalence of OP in male patients with COPD was significantly higher than in those without COPD, and reduced BMD was associated with airflow limitation in male patients with COPD. Similarly, a case-control study showed that COPD was associated with low BMD in the femoral neck in male patients, reporting an OR of 1.5 for OP in COPD male patients compared with controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The logistic regression analyses confirmed that airway obstruction categories were associated with osteopenia/OP, even after adjustment for potential confounding factors, showing that postmenopausal women with COPD may have a higher risk of osteopenia/OP. Our finding may be supported by observations by Sakurai et al 8 , who found that the prevalence of OP in male patients with COPD was significantly higher than in those without COPD, and reduced BMD was associated with airflow limitation in male patients with COPD. Similarly, a case-control study showed that COPD was associated with low BMD in the femoral neck in male patients, reporting an OR of 1.5 for OP in COPD male patients compared with controls.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have clearly indicated OP to be associated with COPD in male patients; however, to date, few studies have examined the relationship between bone mass density (BMD) and COPD in postmenopausal women, remaining a matter of debate 2,8 . The aim of this cross-sectional study was to examine the association between BMD and COPD in postmenopausal women in Northwest China.…”
Section: Introductionmentioning
confidence: 99%
“…Sakurai-Iesato et al [18] concluded that 46% of participants were osteopenic and 14% were osteoporotic. They found that CAT and FEV1 scores were correlated with BMD of patients with COPD.…”
Section: Resultsmentioning
confidence: 99%
“…Osteoporosis is one of the systemic effects of COPD, though the causal relationship and molecular association between COPD and osteoporosis has yet to be established [4] . It is commonly found in COPD patients and its prevalence is higher in these patients than in healthy subjects and those with various other chronic lung diseases such as asthma, idiopathic pulmonary fibrosis, pulmonary hypertension, sarcoidosis, scleroderma or Kartagener's syndrome and bronchiectasis [7][8][9][10][11]. Osteoporosis is also more prevalent in women than in men [11] .…”
mentioning
confidence: 99%
“…Routine screening and management for osteoporosis in COPD patients enables physicians to diagnose this disorder at an early phase to reduce its negative consequences. However, some studies only have found the degree of reduced bone mineral density (BMD) to be comparable to the severity of airflow limitation [7][8][9][10] , meaning that measurement of BMD might not be a good index or sensitive enough tool to determine the degree of bone loss in COPD patients. Additionally, there have been few studies conducted in Thailand regarding the prevalence of osteoporosis and osteopenia and their association with COPD severity.…”
mentioning
confidence: 99%